Vegetais cultivados em quintais rurais piauienses com indicação anticâncer: Uma busca pelo conhecimento tradicional - Abreu, Maria Carolina de; Silva, Paulo Henrique da; Oliveira, Ykaro Richard (Ciência e Natura, 2016)
The aim of this study was to identify the medicinal plants with anticancer indication grown in backyards by residents of the rural community Aroeiras, Monsenhor Hipolito - PI. It was conducted a field research with quali-quantitative approach in the period February to May 2014, in which were executed semi-structured interviews with selected residents by sampling "snowball". The tour-guided technique was used in monitoring of backyards and simultaneous to the data collection, samples were collected from the mentioned plants, which were herborized according to standard techniques in plant taxonomy. In all, they investigated 71 backyards, with a sample of 71 respondents, where 38.02% reported cultivate some vegetable indicated for the prevention or treatment of cancer. Thus, in backyards were raised 6 species: Morinda citrifolia L. (55.55%), Aloe vera (L.) Burm. F. (37.03%), Annona muricata L (14.81%), Euphorbia tirucalli L. (11.11%), Chenopodium ambrosioides L. (3.70%) and Capsicum frutescens L. (3.70 %), noting in this way, the persistence of vegetable cultivation for medicinal purposes in the locality studied, however, is remarkable the need for clarification of the danger of indiscriminate use of such vegetables as the prevention the worsening of the disease.